Racial and ethnic variation in multigene panel testing in a cohort of BRCA1/2‐negative individuals who had genetic testing in a large urban comprehensive cancer center. (17th January 2022) - Tatineni, Sushma; Tarockoff, Meri; Abdallah, Nadine; Purrington, Kristen S.; Assad, Hadeel; Reagle, Rachel; Petrucelli, Nancie; Simon, Michael S.
Abstract: Background: There is sparse clinical information on the racial and ethnic distribution of results of multigene panel testing among individuals at high risk for hereditary cancer. Methods: We evaluated the results of multigene panel testing across eight clinical sites across the state of Michigan for individuals seen for genetic counseling from May 13, 2013 to October 31, 2019 at the Karmanos Cancer Institute's cancer genetics clinic. We estimated the prevalence of pathogenic variants and variants of uncertain significance (VUS) from genes other than BRCA1 / 2 among individuals of non‐Hispanic White (NHW), Black or African American (AA), Ashkenazi Jewish (AJ), Arab, Hispanic, and other ancestry. Results: The racial and ethnic distribution of 2419 individuals who had panel testing included 68.8% NHW, 22.1% AA, 2.3% Arab, 2.2% AJ, 1.0% Hispanic, and 3.6% other. Of these, 11.2% had pathogenic variants and 17.5% had VUS. After multivariable analyses, compared to NHW, AA were less likely to have pathogenic variants (OR 95% CI, 0.38, 0.24–0.59, p < 0.001). Both AA and Arabs were more likely to have VUS (OR 95% CI, 1.53, 1.18–1.98, p = 0.001 and OR 95% CI, 2.28, 1.17–4.43, p = 0.015, respectively). There were no significant differences for other groups. The most common pathogenic variants were CHEK2 ( n = 65), MUTYH ( n = 45), ATM ( n = 28), and MSH2 ( n = 22); the most common pathogenic variants by race and ethnicity were CHEK2 (NHW), MSH2 and MUTYH (AA), MSH2 (Arab), MSH6 and CHEK2 (AJ), and MLH1 (Hispanic); the most common pathogenic variants by primary cancer site were CHEK2 (breast), MSH2 (colon), BRIP1 and MUTYH (ovarian), and MSH2 and MSH6 (endometrial). Conclusions: Understanding the racial and ethnic distribution of pathogenic variants in multi‐gene panels has the potential to lead to better identification of individuals at risk for hereditary cancer. Abstract : Racial and ethnicity variations were described in patients undergoing multi‐gene panel testing. In addition, common pathogenic variants based on race/ethnicity as well as cancer type was described. This descriptive study allows for informed decisions in counseling of patients.